The Indolic Diet-Derivative, 3, 3′-Diindolylmethane, Induced Apoptosis in Human Colon Cancer Cells through Upregulation of NDRG1. (13th November 2011) - Lerner, A.; Grafi-Cohen, M.; Napso, T.; Azzam, N.; Fares, F.
Abstract : N-myc downstream regulated gene-1 participates in carcinogenesis, angiogenesis, metastases, and anticancer drug resistance. In the present study, we analyzed the expression pattern of N-myc downstream regulated gene-1 following treatment of human colonic cancer cell lines; HCT-116 (well differentiated with wild-type p53 gene) and Colo-320 (poorly differentiated with mutant p53 gene), with 3, 3′-diindolylmethane, a well-established proapoptotic agent product derived from indole-3-carbinol. Treatment of Colo-320 and HCT-116 with 3, 3′-diindolylmethane disclosed inhibition of cell viability in a dose-dependent manner, mediated through apoptosis induction. The increased expression of N-myc downstream regulated gene-1 was detected only in poorly differentiated colon cancer cells, Colo-320 cell line. Our results suggest that N-myc downstream regulated gene-1 expression is enhanced by 3, 3′-diindolylmethane in poorly differentiated cells and followed by induction of apoptosis. 3, 3′-diindolylmethane induced apoptosis may represent a new regulator of N-myc downstream regulated gene-1 in poorly differentiated colonic cancer cells.